2015
DOI: 10.1111/age.12328
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in dopamine receptor D4 gene is associated with pigeon racing performance

Abstract: Figure 1 Principal component analysis on LD-pruned data set of 12 013 SNP loci across 66 individuals (one outlier from the Appaloosa breed removed). PCs 1 and 2 explain 2.08 and 2.05% of the variation respectively. QH, Quarter Horse. ECA1, 62.5 kb from TRPM1, also had a high F ST in pairwise comparisons including the Appaloosa. Therefore, although the divergence between breeds is low, these results are evidence that genomic signatures of selection for major, breed-defining phenotypes in the Appaloosa can be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…Nowadays, numerous pigeon breeds are known, and some are used for either meat production, such as ornamental birds, or for pigeon sports (carrier pigeons) [ 3 ]. The carrier pigeons are used extensively for racing, and various studies have explored the influence of genetics and dietary parameters as well as infections on race performance [ 4 , 5 , 6 , 7 ]. The races have a very high physical burden on racing pigeons as they are held every week for 4 consecutive months with racing distancing ranging from 100 to 1000 km [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, numerous pigeon breeds are known, and some are used for either meat production, such as ornamental birds, or for pigeon sports (carrier pigeons) [ 3 ]. The carrier pigeons are used extensively for racing, and various studies have explored the influence of genetics and dietary parameters as well as infections on race performance [ 4 , 5 , 6 , 7 ]. The races have a very high physical burden on racing pigeons as they are held every week for 4 consecutive months with racing distancing ranging from 100 to 1000 km [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…We had surveyed 5-HTT exon1 and ATP6 among Japanese racing pigeons but we couldn’t find polymorphism within these two genes (data not shown). Future functional genomics and linkage analyses must include more candidate genes (e.g., dopamine receptor D4 [ 17 ] or LDHA coding exons [ 23 ]) and more racing pigeon populations to confirm the relationship between genetic variation and complex traits such as survivability. Nonetheless, the microsatellite locus reported here should prove useful for marker-assisted selection that can maximize the genetic quality of racing pigeons and will further our knowledge regarding the genetic underpinnings of survivability and navigation ability in wild migrating bird species.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic markers have been used to predict racing performance in humans [ 13 ], horses [ 14 ], dogs [ 15 ], and pigeons [ 6 , 16 , 17 ]. These studies have indicated that lactate dehydrogenase isoform A, encoded by the lactate dehydrogenase A gene ( LDHA ), is critical to the aerobic/anaerobic metabolism of different tissues and thus to overall physiological performance.…”
Section: Introductionmentioning
confidence: 99%
“…Each lobe is 50-60 mm long and forms either an H or a U shape, as shown in Figure 1.1 below. It averages 25-30 g in adults, women having heavier glands than men (PubMed Health, 2015).…”
Section: Anatomy Of the Thyroid Glandmentioning
confidence: 99%